Human Resource Management in Nursing: Strategies for Workforce Recruitment, Retention, and Motivation: A Systematic Review - Florence AKINGBESOTE (The Nursing Scope, 2026)
Background: Human resource management (HRM) is essential to nursing workforce sustainability because nurses constitute the largest segment of the healthcare workforce, and their availability, competence, and motivation directly influence the quality and safety of patient care. Despite its importance, nursing workforce management continues to face persistent recruitment shortages, high turnover, and inadequate retention strategies, particularly in rural and resource-limited settings. Aim: This systematic review examined HRM principles, strategies, and challenges influencing nursing workforce recruitment, motivation, retention, and related policy interventions. Method: A systematic review was conducted using evidence from multiple electronic databases and grey literature sources. Eligible studies and policy documents were appraised using the Critical Appraisal Skills Programme (CASP) framework and synthesised thematically to identify evidence-based HRM strategies for nursing workforce recruitment, retention, and motivation. Findings: Ten interconnected HRM domains were identified, including workforce planning, recruitment, retention, motivation, work environment, professional development, performance management, leadership, policy frameworks, and technology integration. Competitive compensation, supportive work environments, professional autonomy, mentorship, and participatory decision-making emerged as key determinants of nurse retention and motivation. Conclusion: Nursing workforce challenges are systemic and require comprehensive HRM strategies supported by effective policies, strong nursing leadership, and sustained organisational investment to strengthen workforce stability and improve healthcare outcomes. Recommendation: Healthcare organisations and policymakers should implement evidence-based HRM strategies that promote workforce planning, supportive leadership, professional development, equitable compensation, and employee engagement. Further research should evaluate these interventions, particularly in low- and middle-income countries. Keywords: Human resource management; nursing workforce; recruitment; retention; motivation; job satisfaction; nurse turnover.